IDENTIFIKASI POTENSI PANAS BUMI MENGGUNAKAN LANDSAT 8 SERTA PENENTUAN LOKASI PEMBANGKIT LISTRIK TENAGA PANAS BUMI (Studi Kasus : Kawasan Gunung Lawu) - Hariyanto, Teguh; Robawa, Farrel Narendra (Departemen Teknik Geomatika ITS, 2016)
Indonesia is located in the meeting point of several tectonic plates that related to the potential of geothermal energy. Geothermal energy in Indonesia spread in Jawa, Sumatra, Sulawesi, Nusa Tenggara, and other provinces. Their surface manifestations such as fumaroles, hot ground, sinter silica, hydrothermal alteration and hot springs is an indicator of geothermal energy. All manifestations of the surface has a relatively higher temperature than the surrounding environment (anomaly). First step to identify geothermal, is to study the characteristics of the potential area (landform). Identifying potential areas of geothermal can be detected using remote sensing (thermal channels) Landsat 8. Thermal channels is very effective to identify geothermal manifestations with wide area of research. The results of the processing of Landsat 8 will generate to temperature anomalies that indicate of heat manifestations. However, these anomalies are not all manifestations of geothermal. Therefore, there should be a further processing with predetermined parameters.Mount Lawu, located in Karanganyar District, Central Java and Magetan District, East Java, has predicted geothermal potential energy. Total potential of geothermal energy was proccess by overlay several parameters; land surface temperature anomalies, vegetation density anomaly, and preliminary survey data. The identification results of Geothermal Potential is 275 MWe . Using geographical information system analysis show that potential area for power plant is 159 920 km2 ( 15992.094 Ha ) and not potential area is 487 560 km2 ( 48756.068 Ha).